2012
DOI: 10.1007/s00038-012-0396-3
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the intention of preconception care use: lessons from a multi-ethnic urban population in the Netherlands

Abstract: Modifiable determinants as attitude and barriers can be addressed to enhance preconception care attendance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
4
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 35 publications
3
31
4
2
Order By: Relevance
“…Tamal et al also found no relationship between the level of education and intention to seek PCC (35). This may indicate that services and information related to PCC are provided by centers.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Tamal et al also found no relationship between the level of education and intention to seek PCC (35). This may indicate that services and information related to PCC are provided by centers.…”
Section: Discussionmentioning
confidence: 96%
“…Tamel et al also showed that employed women have a lower tendency to engage in pre-pregnancy care (35). This can be due to the working times of healthcare centers, which might interfere with the working hours of employed women.…”
Section: Discussionmentioning
confidence: 99%
“…[9 , 10] Third, different pilot projects in the GP and midwife settings have taken place which show positive attitudes of Dutch women towards PCC consultations. [11][12][13] Lastly, prior audits show positive ambitions of GPs and midwives to deliver PCC. Despite the aforementioned developments, PCC consultations remain scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Opvallend was dat roken vooral voorkwam bij Turkse (34%) en Antilliaanse (43%) respondenten, en nauwelijks onder Marokkaanse (1%) respondenten. 4 Doelgroep-specifieke PCZ voorlichting richtte zich op cursussen voor vrouwen en mannen van niet-Nederlandse afkomst (in bijvoorbeeld zogenaamde 'Tupperware' bijeenkomsten). Belangrijke cursuskenmerken waren het aanleren om regie te nemen en (daarmee) bereiken van reële gedragsverandering.…”
Section: Preconceptiezorgunclassified